Adopting Clinical Guidelines for Admission Criteria of Intensive Care Unit: A Measure to Manage Queues of Patients Waiting for This Section - Mohammad Alizadeh, Afshin; Abolghazi, Maryam; Dabbagh, Ali; Malek, Bahman; Yazdi-Nezhad, Homeira (Novelty in Biomedicine, 2018)
Background: Due to the need of patients to the intensive care unit (ICU) for receiving medical and nursing services, these services should be provided in a timely manner. This study aimed to develop the clinical guidelines for admission criteria of intensive care unit. Materials and Methods: This study was observational type study was conducted for nine months in 2015 based on a three-step process of adoption of clinical guidelines including planning, adoption and finalization. After conducting systematic searches, the quality of retrieved clinical guidelines was evaluated by experts from policy makers in the admission of patients in the ICU. Finally, the ultimate version of the guideline was developed after reviewing and organizing expert panel sessions. Results: The criteria for accepting patients were presented in form of seven clauses based on the neurological status, cardiovascular status, respiratory status, water and electrolyte disorders, gastrointestinal disturbances, endocrine disorders, surgery and postoperative care. Conclusion: One of the most important factors of creating demand inducing to the patients is the lack of clinical guidelines. It is recommended that departmental doctors should apply the mentioned clinical guidelines in order to make the resources of the intensive care unit more effective.